Modeling Business Performance and Macroeconomic Factors to Explain Stock Market Returns in LQ45 Indonesia Stock Exchange (IDX) - Benny Budiawan Tjandrasa (Master of Management, School of Business and Management, Petra Christian University, 2019)
The purpose of this study is to confirm the effect of business performance and macroeconomics on stock returns in the industrial sector in the Indonesia Stock Exchange LQ45 index. This study examines eight variables from business performance and macroeconomics, namely: current ratio, debt-equity ratio, total asset turnover, return on equity, inflation rate, interest rate, exchange rate, and political stability to be tested for the effect on the stock return of the industrial sector. Using Generalized Least Square techniques, it is concluded that the Industrial sector in the Indonesia Stock Exchange is strongly influenced by macroeconomic factors rather than business performance factors. This is common in capital markets which are mostly dominated by foreigners because foreign investors are very sensitive to changes in a country's macroeconomic conditions especially if it is related to political conditions. From the iteration results, there are two multivariate regression models which are statistically considered the most suitable. The originality of this study is to prove statistically that political stability is very influential on LQ45 stock returns in the industrial sector on the Indonesia Stock Exchange